تطبيق الانستغرام ودوره في تعزيز مشاركة طلاب الجامعات لتحقيق الاستدامة البيئية – طلبة كلية التربية الأساسية في جامعة الكوفة انموذجا - الغانمي, أمجد عبد الأمير (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The research problem is represented by the role played by the Instagram application in order to enhance the participation of university students to achieve environmental sustainability. The research aims to identify the most important specialized pages that students follow and to uncover social media applications in order to achieve environmental sustainability. The questionnaire was adopted as a tool for collecting data, and the sample was chosen intentionally. It consisted of (512) university students at the University of Kufa, College of Basic Education, from its four departments (Arabic language, Islamic education, kindergarten, and mathematics): and the research reached a number of conclusions, including, The application includes a database and pages related to environmental affairs that can be used to achieve environmental sustainability. The university youth segment has a major role in spreading the culture of environmental awareness among society in order to achieve environmental sustainability. This comes through their follow-up of media applications, their use of many social media pages, official and semi-official government websites, newspaper and magazine websites, and specialized and non-specialized websites, and their holding of seminars, workshops, dialogues, and panel discussions.